2020
DOI: 10.3390/ijerph17197239
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Probiotics to Anti-Obesity Therapy by Percutaneous Electrical Stimulation of Dermatome T6. A Pilot Study

Abstract: Obesity is becoming a pandemic and percutaneous electrical stimulation (PENS) of dermatome T6 has been demonstrated to reduce stomach motility and appetite, allowing greater weight loss than isolated hypocaloric diets. However, modulation of intestinal microbiota could improve this effect and control cardiovascular risk factors. Our objective was to test whether addition of probiotics could improve weight loss and cardiovascular risk factors in obese subjects after PENS and a hypocaloric diet. A pilot prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…microbiota, and phylum Bacteroidetes (Prevotella spp. ), and a reduction in Firmicutes/Bacteroidetes ratio; clinically, they induced a further reduction in body weight and plasma A1C, triglycerides, and HDL-cholesterol [36].…”
Section: Discussionmentioning
confidence: 93%
“…microbiota, and phylum Bacteroidetes (Prevotella spp. ), and a reduction in Firmicutes/Bacteroidetes ratio; clinically, they induced a further reduction in body weight and plasma A1C, triglycerides, and HDL-cholesterol [36].…”
Section: Discussionmentioning
confidence: 93%
“…Most clinical series and RCTs have been conducted comparing active PENS + diet versus diet alone or against other neuromodulation strategies 30,33–35 . One study showed that adding probiotics to PENS + diet may improve outcome 75 . Even though significant differences were reported when PENS + diet was compared to diet alone, these studies presented a confounding factor of patients receiving Pstim through a needle placed in specific dermatomes, whereas controls were not given a sham intervention.…”
Section: Resultsmentioning
confidence: 99%
“…The risk of bias was moderate in a case series using occipital nerve stimulation 29 and critical for two PENS studies in which stimulation was given along with a hypocaloric diet. 35,76 Of the six RCTs included, five had a high risk of bias 30,31,33,34,75 because controls were not given sham neuromodulation or patients were unblinded towards treatment. One RCT raised serious concerns because obesity was not the primary outcome.…”
Section: Serious Outcome Of Dropouts Not Accountedmentioning
confidence: 99%
See 2 more Smart Citations